Knowledge about antineoplastic drugs: implications for the health of nursing workers in a general hospital - Kely Cristine Batista; Kayo Henrique Jardel Feitosa Sousa; Cristiane Aguiar da Silva Ruas; Regina Célia Gollner Zeitoune (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to understand, from a worker's health perspective, the knowledge of nursing professionals about the use of antineoplastic drugs in a general hospital. Methods: a descriptive and exploratory study with a qualitative approach. It was conducted at a university hospital, between April and August 2018, with 35 nursing professionals who responded to a semi-structured interview. Thematic analysis was used for data treatment. Results: from the data, three thematic categories emerged, related to the nursing professionals' knowledge about antineoplastic drugs and their effects on workers' health; situations in which exposure to these drugs occurs; and protection mechanisms for the patient, the environment, and the worker. Final Considerations: the nursing professionals had little knowledge about antineoplastic drugs. The practices related to handling and the necessary protective measures to deal with these drugs were empirically determined and relatively subsidized the knowledge acquired by the professionals.